Design and Evaluation of Google Sites–Based Learning Media to Teach Biographical Text Identification - Tia Putriana; Nursaid Nursaid (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective learning in the digital era requires instructional media that are interactive, accessible, and aligned with student learning preferences. In Indonesian language instruction, particularly in teaching biographical texts, conventional methods often fail to engage students. This study aims to develop and evaluate Google Sites–based learning media for improving students’ ability to identify biographical texts. This research employed a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved 24 tenth-grade students at MAN 1 Pesisir Selatan. Instruments included needs and curriculum analysis questionnaires, expert validation forms, practicality questionnaires, objective tests (pretest-posttest), and field notes. Media validity was assessed by experts in media, language, and pedagogy, while practicality and effectiveness were evaluated through user feedback and statistical testing. The media was rated highly valid, with expert scores of 86.15% (media), 95% (language), and 96.36% (pedagogy). Practicality assessments yielded scores of 94.67% (teachers) and 90.47% (students), indicating high usability and engagement. A paired sample t-test showed a significant improvement in student performance (p 0.001) from pretest to posttest, confirming the media’s effectiveness. The findings demonstrate that Google Sites-based media is a valid, practical, and effective tool for teaching biographical texts. It supports digital literacy and offers a scalable solution for blended and remote learning. The media serves as a promising alternative to traditional resources, fostering greater comprehension and learner autonomy in secondary education.